2011
DOI: 10.1016/j.biopsycho.2010.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cingulate cortex volume and emotion regulation: Is bigger better?

Abstract: Emotion dysregulation is a key feature of mood and anxiety disorders. Many of these disorders also involve volumetric reductions in brain regions implicated in emotion regulation, including the dorsal anterior cingulate cortex (dACC). Investigating this relationship in healthy individuals may clarify the link between emotion regulation and volumetric reductions in this key brain region. High-resolution anatomical MRI images were used to calculate dACC volumes in 50 healthy female subjects. Trait measures of em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
64
1
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 26 publications
12
64
1
4
Order By: Relevance
“…Consistent with this possibility, exploratory partial correlation analyses in the current study indicated that increased cortical thickness in the ACC of high-risk girls was significantly associated with improved expression and regulation of sad emotions. This pattern of a positive association between ACC gray matter and adaptive responding to negative emotions is consistent with findings of a recent study of never-depressed adults (Giuliani, Drabant, & Gross, 2011) and with results of a study that found that a less severe course of depression was associated with significantly thicker ACC gray matter (Frodl, Jäger, et al, 2008). …”
Section: Discussionsupporting
confidence: 91%
“…Consistent with this possibility, exploratory partial correlation analyses in the current study indicated that increased cortical thickness in the ACC of high-risk girls was significantly associated with improved expression and regulation of sad emotions. This pattern of a positive association between ACC gray matter and adaptive responding to negative emotions is consistent with findings of a recent study of never-depressed adults (Giuliani, Drabant, & Gross, 2011) and with results of a study that found that a less severe course of depression was associated with significantly thicker ACC gray matter (Frodl, Jäger, et al, 2008). …”
Section: Discussionsupporting
confidence: 91%
“…The summed score for the six reappraisal items (e.g., “When I want to feel more positive emotion, I change the way I’m thinking about the situation”) was used specifically, because unlike suppression, which is also measured by the Emotional Reappraisal Questionnaire, cognitive reappraisal has been associated with both the function and structure of the dACC (Giuliani et al, 2011; Ochsner and Gross, 2005). …”
Section: Methodsmentioning
confidence: 99%
“…This region has been previously implicated in cocaine craving and dependence (Wexler et al, 2001) and is involved in inhibitory 'top-down' emotional and cognitive-control processes (Etkin et al, 2006;Chiew and Braver, 2011;Giuliani et al, 2011). Cognitivecontrol mechanisms naturally develop with age in typical development (Crone et al, 2004), and may be particularly relevant for the generation of appropriate coping strategies in response to substance-using situations (Rando et al, 2013).…”
Section: Neural Responses To Favorite-food Cuesmentioning
confidence: 99%